Free composite and chimeric anterior lateral thigh flaps in covering secondary soft tissue defect after tumor resection: an overview from the medical literature to clinical applications - Le, Hong Phuc; Phung, Nguyen; Tran, Nhat Tien; Le, Nghi Thanh Nhan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Objective: To evaluate the results of soft tissue defect treatment with ALT composite flaps in covering secondary soft tissue defects after radical tumors resection. Method: From October 2017 to April 2023, we performed a series of 10 single-stage surgeries using composite anterior lateral thigh flap to cover secondary tissue defects in 2 cases covered Achilles tendon defects and 8 cases covered secondary defects after resection of tumors. In all patients with complex, multi-site secondary defects, in patients with secondary defects after resection of the head of the face, the defects are often complex, multi-plane, and multi-site, requiring the use of flaps flexibly and practicably to provide the best postoperative results for the patient. In 10 clinical cases, complex or clustered anterior femoral flaps were selected, and the pedicle and perforating artery branches were identified by hand-held Doppler. The identification of the perforating branches also helps to define the bounds of the flap. The flap is thinned if too thick. Microsurgery anastomosis was performed before the defect was covered. Result: The size of the ALT flap ranges from 10 x 5cm to 15 x12 cm and the size of the Fascia lata (FL) flap ranges from 7 x 4 cm to 10 x 8 cm. The average peduncle length for skin flap and muscle flap is about 2.5-5 cm and about 3.5- 7 cm, respectively. The thickness of the flap is about 6-13mm. After 3 months of surgery, all flaps are completely alive, close results of flaps are good, distant results are good with stable wound healing, most patients are satisfied with flap color, soft flap site, normal limb function. Conclusion: The free ALT composite chimeric flaps become a viable and flexible option for single-stage, threedimensional reconstruction of complex organ defects after tumor resection, by reducing the number of surgeries and the number of anastomosis. Improving treatment results for complex defects after cancer resection as well as reduce surgery and treatment time.